1984
DOI: 10.1093/infdis/150.6.841
|View full text |Cite
|
Sign up to set email alerts
|

Avian-Human Reassortant Influenza A Viruses Derived by Mating Avian and Human Influenza A Viruses

Abstract: Reassortant influenza A viruses were produced by mating an avian virus (A/Mallard/NY/78, A/Mallard/Alberta/78, or A/Pintail/Alberta/79) with a wild-type human influenza A virus. From each mating a reassortant virus was obtained that contained the genes coding for the hemagglutinin and neuraminidase surface antigens of the human influenza A wild-type virus and the six other RNA segments ("internal genes") of the avian influenza A virus parent. The avian-human reassortant influenza viruses produced resembled the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Generally, in experimental infections, avian influenza viruses replicate poorly in humans and vice versa (Beare and Webster, 1991; Hinshaw et al, 1984; Murphy et al, 1984; Webster et al, 1978) because host restriction constrains interspecies transmission. Recently, however, a newly emerged H7N9 avian influenza virus appeared to break this host barrier and directly infect humans in China, resulting in a total of 238 confirmed cases and 57 fatalities as of 26 Jan 2014 (unofficial statement; http://www.cidrap.umn.edu/news-perspective/2014/01/eleven-new-h7n9-cases-include-one-beijing).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, in experimental infections, avian influenza viruses replicate poorly in humans and vice versa (Beare and Webster, 1991; Hinshaw et al, 1984; Murphy et al, 1984; Webster et al, 1978) because host restriction constrains interspecies transmission. Recently, however, a newly emerged H7N9 avian influenza virus appeared to break this host barrier and directly infect humans in China, resulting in a total of 238 confirmed cases and 57 fatalities as of 26 Jan 2014 (unofficial statement; http://www.cidrap.umn.edu/news-perspective/2014/01/eleven-new-h7n9-cases-include-one-beijing).…”
Section: Discussionmentioning
confidence: 99%
“…Early in vivo studies indicated that the M gene plays roles in the growth control of influenza virus in embryonated eggs and squirrel monkeys [2,22,30], and in the neurotropism in mouse brain [24]. The M gene of influenza viruses encodes 2 proteins, M 1 and M2 [17,20].…”
Section: Discussionmentioning
confidence: 99%
“…The origin of RNA segments of each reassortant virus was determined by measuring RNA size by polyacrylamide gel electrophoresis (PAGE) [22]. Viral RNA was extracted from purified virions with phenol :chloroform (1 : 1) and precipitated with ethanol.…”
Section: Genotype Analysismentioning
confidence: 99%
“…Co-infection step plays a key role in the classical genetic reassortment. Multiple studies have attempted to evaluate reassortment efficiencies of wild-type and cold-adapted viruses using different variants of crossing procedures, such as simultaneous [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] or successive [27][28][29] inoculation of two parental viruses. Co-infection procedures also differed by infectivity ratio of the viruses, temperature of incubation and culturing substrate (eggs or cell culture).…”
Section: Co-infection Proceduresmentioning
confidence: 99%
“…Co-infection procedures also differed by infectivity ratio of the viruses, temperature of incubation and culturing substrate (eggs or cell culture). Most of the recent studies describe reassortment of live parental viruses [11][12][13][14][15]20,[22][23][24][25][26]. However, the reassortment efficiency can be substantially improved if one of the parental viruses is inactivated prior to co-infection.…”
Section: Co-infection Proceduresmentioning
confidence: 99%